Cluster Change Analysis to Assess the Effectiveness of Speaking Skill Techniques using Machine Learning - Wulandari, Nunik Herani; Purwayoga, Vega (International Journal of Applied Sciences and Smart Technologies, 2025)
This study aims to compare effective teaching methods for speaking using machine learning. The classes used in this study consisted of three classes: conventional, vlog project, and picture series. The data used were students' pre-test and post-test scores. The machine learning algorithm used is K-Means. K-Means clusters the pre-test and post-test data. The results of K-Means clustering on the pre-test and post-test identified the differences in student groups between the pre-test and post-test. Students who experienced the most cluster movement were those in the vlog project class, the conventional class, and the picture series class.